The Genetic and Clinical Outcomes in Fetuses With Isolated Fetal Growth Restriction: A Chinese Single-Center Retrospective Study - Zhou, Hang; Cheng, Ken; Li, Yingsi; Fu, Fang; Li, Ru; Zhang, Yongling; Yang, Xin; Jing, Xiangyi; Li, Fucheng; Han, Jin; Pan, Min; Zhen, Li; et al. (Frontiers in Genetics, 2022)
Objective: To evaluate the utility of a chromosomal microarray (CMA) in fetuses with isolated fetal growth restriction (FGR) and explore risk factors for the prediction of chromosomal aberration and perinatal adverse outcomes. Method: This study included 271 fetuses of estimated fetal weight less than the 3rd percentile without other structural malformation. Early-onset and late-onset FGR were defined as gestational weeks less than 32 weeks and more than 32 weeks respectively. These patients underwent quantitative fluorescent polymerase chain reaction (QF-PCR) and CMA as the first-line genetic detection strategy. Chromosomal anomalies were compared after stratified analysis by the early-onset and the late-onset FGR, including the absence or presence of ultrasound soft markers, abnormal amniotic fluid, abnormal umbilical Doppler, and gestational disorders. The follow-up time was within 1 year after birth. Logistic regression was used to seek risk predictors of chromosomal aberration and perinatal adverse outcomes for isolated FGR. Results: The CMA identified clinically significant variants in 18/271 (6.6%) fetuses, and variants of unknown significance (VOUS) in 15/271 (5.5%) fetuses. Stratified analysis showed that there was a higher incidence of clinically significant variants in fetuses with the early-onset FGR compared with late-onset FGR (8.7%, 17/195 vs. 1.3%, 1/76, p < 0.05). Regression analysis showed that early gestational age (GA) at diagnosis of FGR was the major risk factor for chromosomal aberration (OR = 0.846). By variable regression analysis, early GA at diagnosis and decreased estimated fetal weight (EFW) percentile of suspicion of FGR, asymmetrical FGR, abnormal amniotic fluid, and severe preeclampsia could all increase the risk of adverse outcomes of isolated FGR including intra-uterine fetal death (IUFD), termination of pregnancy (TOP), and preterm birth in pregnancies with FGR. Conclusion: This study emphasized the value of microarrays for unbalanced genomic variants in fetuses with isolated FGR, especially since the gestational age of nullipara was less than 32 weeks. Perinatal adverse outcomes of isolated FGR were influenced by multiple factors including GA and estimated fetal weight (EFW) percentile of suspicion of FGR, asymmetrical FGR, abnormal amniotic fluid, and severe preeclampsia.